1993
DOI: 10.1002/jmv.1890410527
|View full text |Cite
|
Sign up to set email alerts
|

Review of research leading to new anti-herpesvirus agents in clinical development: Valaciclovir hydrochloride (256u, the L-valyl ester of acyclovir) and 882c, a specific agent for varicella zoster virus

Abstract: Research leading to the new anti-herpesvirus compounds discussed here has come from three approaches. The first approach was directed towards improving the bioavailability of acyclovir by examining the potential of a variety of prodrugs, leading to the new compound valaciclovir hydrochloride. The second approach was to examine a large number of 5-substituted pyrimidines for activity against those viruses which were not as potently inhibited by acyclovir as are herpes simplex viruses, i.e., varicella zoster vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Serum levels and area under the curve (AUC) are comparable to those achieved with intravenous acyclovir. [13][14][15] Recent prospective randomized studies using valacyclovir for the prophylactic treatment of CMV infection have shown safety and efficacy in patients with renal transplants and AIDS. [16][17][18][19] However, the benefit of this approach for CMV prophylaxis in SCT recipients has not been reported.…”
mentioning
confidence: 99%
“…Serum levels and area under the curve (AUC) are comparable to those achieved with intravenous acyclovir. [13][14][15] Recent prospective randomized studies using valacyclovir for the prophylactic treatment of CMV infection have shown safety and efficacy in patients with renal transplants and AIDS. [16][17][18][19] However, the benefit of this approach for CMV prophylaxis in SCT recipients has not been reported.…”
mentioning
confidence: 99%
“…70 Nevertheless, efficiencies of these compounds as inhibitors of EBV are limited. To improve bioavailability, the orally available prodrugs valaciclovir (VACV), 71 valganciclovir (VGC; the valine ester of GCV) 72 and famciclovir (FCV) 73 have been introduced in the mid-1990s. VACV, the L-valyl ester of ACV, is rapidly and almost completely converted to ACV in vivo, as well as provided three to five times increase in ACV bioavailability.…”
Section: Nucleoside Analoguesmentioning
confidence: 99%
“…The fi rst group includes acyclic nucleoside/nucleotide analogues and pyrophosphate analogues, the target of which is the EBV DNA polymerase. Despite their effi cient inhibition of the viral polymerase in vitro in tissue culture experiments, they have displayed limitations by toxic side effects, poor oral bioavailability, and emergence of drug-resistant virus strains in in vivo treatment (Pagano et al, 1983;Purifoy et al, 1993). Recently, through further searching for new therapeutic compounds with the enhanced specifi city in their antiviral action, a second group demonstrating unique modes of action has become available, which contains compounds of a mixed nature with divergent structures.…”
Section: Ebv Infection and Antiviral Drugsmentioning
confidence: 99%